2020
DOI: 10.31584/jhsmr.2020764
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Hepatectomy as a Safe Approach for Synchronous Colorectal Liver Metastasis

Abstract: Objective: The optimal surgical strategy for treatment of colorectal cancer with synchronous liver metastasis remains controversial. This retrospective analysis compared both surgical and perioperative outcomes for patients receiving simultaneous hepatectomy and primary colorectal surgery, to those receiving hepatectomy alone for stage approach. Material and Methods: Between; June, 2013 and June, 2019, 111 patients underwent a hepatectomy for synchronous liver metastasis, from this 90 patients received stage r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
(21 reference statements)
0
2
1
Order By: Relevance
“…Regarding the length of stay (LOS), the overall median LOS was 5 days, and the median LOS values of patients with and without AEs were 7 and 5 days, respectively. In our previous study on colorectal liver metastasis, the group of patients represented open surgery; the median LOS was 7 days25 and seemed longer than the present laparoscopic liver surgery study consisted with the evidence from a meta-analysis indicated that LLR had a shorter LOS than open surgery 4. However, in the present study, the benefit of LLR in terms of faster recovery time is preserved only in patients who did not experience AEs.…”
Section: Discussioncontrasting
confidence: 57%
“…Regarding the length of stay (LOS), the overall median LOS was 5 days, and the median LOS values of patients with and without AEs were 7 and 5 days, respectively. In our previous study on colorectal liver metastasis, the group of patients represented open surgery; the median LOS was 7 days25 and seemed longer than the present laparoscopic liver surgery study consisted with the evidence from a meta-analysis indicated that LLR had a shorter LOS than open surgery 4. However, in the present study, the benefit of LLR in terms of faster recovery time is preserved only in patients who did not experience AEs.…”
Section: Discussioncontrasting
confidence: 57%
“…Total hospital stay was reported in 14 articles and the heterogeneity substantially decreased (from 94.3% to 76.9%) after excluding one publication[ 40 ] and thus 13 publications were included in the pooled analysis. The average total hospital stay was five days shorter in the simultaneous resection than in the staged-resection group (WMD = –5.43, 95% CI [− 7.29 to − 3.58], P < 0.001; I 2 = 76.9%; Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1). In total, only 1 RCT [22] and 22 nRCTs [13,14,17,[23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41], comprising a total of 4862 patients (2056 and 2806 cases of simultaneous resection and staged resection, respectively) were included. All the nRCTs had a NOS score ≥ 6 and the RCT had a low bias risk, assessed using RevMan 5.3 (Fig.…”
Section: Resultsmentioning
confidence: 99%